ASUPAN ENERGI DAN PENGGUNAAN ENERGI (ENERGY EXPENDITURE) SELAMA KEHAMILAN: STUDI LONGITUDINAL - Rosmalina, Yuniar; Safitri, Amalia; Ernawati, Fitrah (GIZI INDONESIA, 2014)
Selama kehamilan, asupan gizi seharusnya datang dari makanan yang baik dalam jumlah dan kualitas karena sangat penting untuk perkembangan kehamilan yang sehat. Selain itu keadaan kesehatan ibu selama kehamilan sangat mempengaruhi perkembangan janin, Tujuan tulisan ini adalah membandingkan energi yang masuk dengan energi yang dikeluarkan dalam melakukan kegiatan sehari. Penelitian ini adalah longitudinal yang mengikuti respondents dalam kaitannya dengan asupan energi dan pengeluaran energi dari usia kehamilan 3 bulan sampai usia 8 bulan dengan melakukan. Jumlah responden pada awal studi di trimester pertama (awal rekruitment) adalah 334 ibu dan pada akhir studi adalah 262 ibu. Data yang dikumpulkan meliputi karakteristik , berat badan,aktifitas fisik dan konsumsi makanan (melalui recall 1 x 24 jam). Berat badan, aktifitas fisik dan konsumsi makanan dikumpulkan setiap 2 minggu. Hasil menunjukkan bahwa asupan energi dan energi yang dikeluarkan relatif sama. Juga didapat rerata berat badan ibu pada kehamilan yang ke 3 bulan adalah 48,7 kg dan kemudian bertambah sesuai dengan perkembangan kehamilan. Rerata kenaikan berat badan dari usia 3 bulan ke 8 bulan kehamilan asupan energi, adalah 7,5 kg. Asupan energite rendah saat kehamilan 3 bulan yaitu 2000 Kal sehari kemudian meningkat pada kehamilan yang ke 7 bulan dan menurun kembali pada umur kehamilan ke 8 bulan.ABSTRACT ENERY INTAKE AND ENERGY EXPENDITURE DURING PREGNANCY:A LONGITUDINAL STUDY During pregnancy, nutrient intakes should come from both good quality and quantity foods because they are very important for developing healthy pregnancy. In addition to nutrient intake, health status during pregnancy greatly affects fetal development. This paper aims to study a comparison of the energy intake of pregnant women with energy expenditure in performing daily activities . This is a longitudinal study which followed respondents in relation to energy intake and energy expenditure from the age of 3 months until the age of 8 months of pregnancy. The number of respondents at the beginning of the first trimester of pregnancy/initial recruitment) was 334 mothers and the end of the study became262 mothers. Data collected included respondent characteristics (age, education, occupation), body weight, physical activity, nutrient intake using a 24-hour recall method. Body weight, physical activity and food consumption were collected every 2 weeks. The results indicated that energy intake and energy expenditure were at the average per month. Also showed an average maternal weight at the age of 3 months (initial recruitment) was 48.7 kg and the weight increased with increasing gestational age. The average increase in weight in the initial recruitment at the age of 8 months of pregnancy was on 7.5 kg. The lowest energy intake at 3 month pregnancy was 982 kcal per day, then increasing energy intake with increasing gestational age, but the average energy intake was only 50 percent compared to energy expenditure for their daily activities. The average energy expenditure was low at the age of 3 months of pregnancy, about 2000 kcal and increased until the age of 7 months of pregnancy then declined at the age of 8 months of pregnancy.Keywords: energy intake, energy expenditure, pregnant women